The understanding of epidemiology and study designs - Wandile, Pranali (International Journal of Clinical Trials, 2023)
The goal of health care systems is to keep patients healthy by monitoring, diagnosing, and treating their illnesses. These complex systems have many objectives, such as improving the quality of health care, making healthcare accessible to all people who are in need, extending people’s life span, preventing illnesses, etc. Promoting healthy lifestyles along with the prevention of illnesses to improve people’s health is also a fundamental principle of public health, and now it also become a fundamental principle of health care and integrating into health and social care strategies across the world. Epidemiology is the system of ultimate reasoning focused on creating and examining theories in systematic fields such as biology, physics, behavioral sciences. Epidemiology rationalize the health-associated states and events and provide the justification for further suitable real-world public health measures. While working in the field, I observed that allied healthcare professionals lacked basic knowledge about epidemiology and related study designs. The input from this healthcare professional not only assists in building meaningful research studies but also demonstrates its powerful impact on patients’ healthcare through preventive measures and study results. The goal of this article is to provide basic knowledge of epidemiology and its various study designs in a simplistic language to allied healthcare professionals working in the field. In this article, I have described a general overview of epidemiology and various study designs, along with examples. I hope this information could be beneficial for a better understanding of epidemiology to healthcare professionals working in the field.